Divided and united: perceptions of athlete activism at the ESPYS. Issue 12 (2nd December 2019) - Frederick, Evan L.; Pegoraro, Ann; Sanderson, Jimmy
Abstract: The purpose of this study was to examine the framing and re-framing of activism efforts enacted by LeBron James, Dwayne Wade, Chris Paul, and Carmelo Anthony during the 2016 ESPYS through the theoretical lens of critical race theory. Specifically, comments made to three posts on ESPN's Facebook page pertaining to these calls for activism were analyzed. Qualitative coding of 10, 658 comments led to the discovery of four primary themes including (a) discussing race; (b) law enforcement accountability; (c) realities of violence; and (d) debating crime. While the athletes (i.e. the messengers) engaging in activism received attention via Facebook comments, users focused significant attention on the messages being disseminated. Ultimately, this social media discourse illuminated the complex nature of race relations in the United States today, highlighting the persistence of deeply ingrained cultural stereotypes and beliefs that are often left unshaken by athlete activism.